Izpiranje baker-etanolaminskih pripravkov iz lesa - Humar, Miha (Zbornik gozdarstva in lesarstva, 2006)
Copper-ethanolamine based preservatives are successfully replacing classical copper-chromium based preservative solutions. In this paper, the proposed fixation mechanisms are described. Additionaly,basic facts that influence copper leaching from wood are elucidated: composition and concentration of solutions, time and temperature of fixation as well as wood species and treatment method used. The results show that addition of ethanolamine significiantly improves copper fixation, but can on the other hand cause depolymerisation of wood polymers, which results in increased leaching of copper.
Keywords: amini; bakrove spojine; etanolamin; fungicidnost; izpiranje; vezava; zaščita lesa